Tiltott kapcsolat : a magyar-lengyel ellenzéki együttműködés, 1976-1989 - Mitrovits, Miklós; Jaffa Kiadó (Budapest : Jaffa, 2020)
The most significant external influence on the political and cultural opposition of the Kádár era were the events in Poland. When and how did the democratic opposition learn samizdat techniques from the Poles? How did they organize a camp at Lake Balaton for poor Polish children? What was the reception of the Solidarity movement in Hungary?
I. Párhuzamos valóságok -- II. Egy kapcsolat kezdetei -- III. A lengyel Szolidaritás és a magyar ellenzék -- IV. Hadiállapotban -- V. A párt és a társadalom reakciói -- VI. Az 1956-os forradalom emléke és a magyar ellenzék Lengyelországban -- VII. Közép-európaiságunk -- VIII. A Szabadság és Béke mozgalom és a magyar egyetemisták -- IX. A rendszerváltás küszöbén -- X. Kerekasztalok és választások.
Includes bibliographical references (pages 268-275) and index.
Keywords: Government, Resistance to -- Hungary -- History -- 20th century; Government, Resistance to -- Poland -- History -- 20th century; Hungary -- Relations -- Poland; Poland -- Relations -- Hungary; Hungary -- Politics and government -- 1945-1989.; Poland -- Politics and government -- 1945-1980.; Poland -- Politics and government -- 1980-1989.